Autonomous underwater vehicles localisation in mobile underwater networks. (2017) - Wei, Xiaohui; Wang, Xingwang; Bai, Xin; Bai, Sen; Liu, Jun
Autonomous underwater vehicles (AUVs) form mobile underwater networks to conduct underwater surveying missions cooperatively. Due to the severe turbulence caused by water currents, individual AUV has to adjust its heading constantly to ensure reaching destination. The coordinated AUV network increases the size of the surveying area, but leads to bigger challenges on maintaining AUV network locations. In this paper, we consider the localisation problem for AUVs in a mobile multi-hop underwater network. In our approach, to avoid the accumulating errors caused by the inertial measurement units, we periodically re-localise the AUV network through surfacing a set of AUVs as beacons. A beacon AUV surfaces to obtain its accurate location information from external sources, such as satellites, and then submerges to adjust the locations for remaining AUVs through acoustic communication. Simulation result shows that our approach greatly improves the localisation accuracy and energy efficiency of the AUV network.